2020
DOI: 10.2147/opth.s258205
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy of Standard and Accelerated (10 Minutes) Corneal Crosslinking in Keratoconus Stabilization</p>

Abstract: Purpose: To evaluate whether Accelerated CXL for 10 minutes is as effective as standard CXL for 30 minutes for the treatment of progressive keratoconus. Patients and Methods: Eighty-two eyes of 62 patients with keratometry examinations performed before and 6 months after surgery were studied. A total of 39 eyes underwent standard CXL with UVA irradiation of 3 mW/cm 2 for 30 minutes and 32 eyes underwent Accelerated CXL UVA irradiation of 9 mW/cm 2 for 10 minutes. The eyes of all patients had corneal thicknesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Para que haja o fechamento do diagnóstico, deve-se haver avaliação clínica levando em consideração os fatores genéticos e externos ao qual o RN foi exposto, solicitação de ecocardiograma e radiografia do tórax para identificar os achados clínicos e para confirmação, deverá ser feito o cateterismo cardíaco para medição da pressão sanguínea em um determinado lado do coração e na artéria pulmonar (STOCK et al, 2020).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Para que haja o fechamento do diagnóstico, deve-se haver avaliação clínica levando em consideração os fatores genéticos e externos ao qual o RN foi exposto, solicitação de ecocardiograma e radiografia do tórax para identificar os achados clínicos e para confirmação, deverá ser feito o cateterismo cardíaco para medição da pressão sanguínea em um determinado lado do coração e na artéria pulmonar (STOCK et al, 2020).…”
Section: Resultsunclassified
“…Nos casos graves utiliza-se a oxigenação por membrana extracorpórea (ECMO) para melhorar significativamente a oferta de oxigênio para o RN, deste modo, possibilitando que haja melhorias na sua situação clínica e diminuição da sua permanência no âmbito hospitalar. A agilidade nas condutas por partes dos profissionais resulta em maiores chances e oportunidades após a alta hospitalar, ofertando novos desfechos e uma qualidade de vida melhor sem interferir no seu dia a dia (STOCK et al, 2020).…”
Section: Introductionunclassified
“…2 Accelerated CXL, with higher UV-A energy and decreased UV-A exposure time, has shown comparable efficacy and safety with conventional CXL. 3–6…”
mentioning
confidence: 99%
“…2 Accelerated CXL, with higher UV-A energy and decreased UV-A exposure time, has shown comparable efficacy and safety with conventional CXL. [3][4][5][6] Combined CXL with topography-guided photorefractive keratectomy (T-PRK) aims to improve the irregular cornea shape, in addition to controlling disease progression. 7 Previous studies and meta-studies have demonstrated the efficacy of this combined procedure in stabilizing KC, decreasing astigmatism and anterior corneal higher-order aberrations (HOAs) with improved quality of vision and daily functioning.…”
mentioning
confidence: 99%